Macroeconomic Analysis Of Trade Balance In 2013 – 2022 - Kusumah, Anuraga; Suharti, Titing; Prasetia, Angga; Yudhawati, Diah; Widiya, Dede (Moneter: Jurnal Keuangan dan Perbankan, 2024)
This rapid economic change causes the currency exchange rate to fall and the price of basic necessities to increase. The Ordinary Least Square (OLS) method is used to assess the trade balance due to the economic crisis, and the export growth of Indonesia's export destination countries will weaken as a result of the crisis. The domestic purchasing power of Indonesia's export destination countries has also declined as a result of the crisis. Secondary data published by BPS for the period 2013–2022 were used in this study. The data was processed using the SPSS V.27 program, which shows that Indonesia's trade balance cannot be separated from exchange rates, inflation, and interest rates, so that all three variables have an impact on the trade balance simultaneously. The estimation of the trade balance model in Indonesia shows that each independent variable—exchange rate, inflation, and interest rate—has a partial effect on the country's trade balance. The greatest influence of this variable was 57.22% on the country's trade balance, and other variables that were not discussed in the study.